Implementation of the Islamic Dirosah Program as a Foundation Curriculum for Students at MI Nurul Huda, Bengkulu City - Putri Surya Anita (Journal of Primary Education (JPE), 2025)
This study aims to describe the implementation of the Islamic Dirosah program as a foundation curriculum and the obstacles faced by schools in implementing the program and how schools overcome these obstacles. This type of research is field research, namely research conducted directly on a fact that occurs in the field. The design of the research is descriptive qualitative, the study will provide an empirical description of "Implementation of the Islamic Dirosah program on students at MI Nurul Huda, Bengkulu City". The data in the study were obtained through: First, Interviews with Mrs. Jumratul Aini as the principal, Mrs. Desi Nopita Sari as the deputy head of curriculum, and 3 Islamic Dirosah teachers. Second, Observation of Islamic Dirosah program learning activities. Third, Documentation regarding document archives related to the Islamic Dirosah program. The data validity test technique in the study used Data Triangulation, Technique Triangulation, and Time Triangulation. The results of the study showed. First, program planning designed by a team to determine the objectives and strategies of dirosah learning, namely using lecture and peer methods. The proposal for program activation is carried out in a meeting using narratives with related parties. Second, organizing the program by appointing personnel with religious competence as dirosah teachers. Third, implementing the program by providing student motivation with a reward and punishment strategy. Fourth, program evaluation using periodic reports every 3 months and taking corrective actions if there are deviations from the program. Meanwhile, program constraints are learning motivation and student discipline, communication between parents and teachers, and inadequate facilities to support dirosah learning.